2008
DOI: 10.1080/08927020801930547
|View full text |Cite
|
Sign up to set email alerts
|

Quantum electron transport in toroidal carbon nanotubes with metallic leads

Abstract: A recursive Green's function method is employed to calculate the density-of-states, transmission function, and current through a 150 layer (3,3) armchair nanotorus (1800 atoms) with laterally attached metallic leads as functions of relative lead angle and magnetic flux. Plateaus in the transmissivity through the torus occur over wide ranges of lead placement, accompanied by enhancements in the transmissivity through the torus as magnetic flux normal to the toroidal plane is varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…11 12 Toroidal carbon nanostructures or carbon nanotori, could play interesting roles in nanoscale device applications in areas such as nanoelectronics, quantum computing and biosensors. 13 14 In addition, these structures could have potential applications in diverse fields such as quantum electronic transport 15 and hydrogen storage materials. 16 Future studies are needed to explain these properties.…”
Section: Introductionmentioning
confidence: 99%
“…11 12 Toroidal carbon nanostructures or carbon nanotori, could play interesting roles in nanoscale device applications in areas such as nanoelectronics, quantum computing and biosensors. 13 14 In addition, these structures could have potential applications in diverse fields such as quantum electronic transport 15 and hydrogen storage materials. 16 Future studies are needed to explain these properties.…”
Section: Introductionmentioning
confidence: 99%
“…An important geometry intensively studied in the last years is the torus surface. Curvature effects plays an important role in toroidal geometry [20]. Toroidal carbon nanotubes, also known as carbon nanotori, appears in nanoelectronics, quantum computing, and biosensors [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to investigate the structural models of tori CNTs to investigate their thermodynamic stabilities. The work of Ihara et al showed that the tori CNTs are found to be more stable than the C 60 fullerene, comparing the cohesive energies. , Additionally, many numerical simulations have demonstrated that the toroidal SWNTs (TSNs) exhibit quantum interference effect in charge transport under an external magnetic field or electromagnetic field, along their potential use as a macroscopic molecular toroid/coil with the molecular Aharonov–Bohm oscillator, spin-polarized current injector, detection of biopolymers, and metal–insulator transition switching. Recently, gold nanoparticles (Au NPs) were deposited on CNT rings for theragnostic applications . Nevertheless, the experimental studies and applications of TSNs have been dilatory as the theoretical investigations .…”
Section: Introductionmentioning
confidence: 99%